Design of steel-concrete composite bridges to eurocodes - Vayas, Ioannis; Iliopoulos, Aristidis (CRC Press, Taylor & Francis Group, 2014)
The book addresses the design for a majority of composite bridge superstructures and guides readers through the selection of appropriate structural bridge systems. It introduces the loads on bridges and their combinations, proposes software supported analysis models, and outlines the required verifications for sections and members at ultimate and serviceability limit states, including fatigue and plate buckling, as well as seismic design of the deck and the bearings. It presents the main types of common composite bridges, discusses structural forms and systems, and describes preliminary design aids and erection methods. It provides information on railway bridges, but through the design examples makes road bridges the focal point